Analisis - Jesikapna Callia Br Guru Singa; I Wayan Nuarsa; I Gusti Ngurah Putra Dirgayusa (Journal of Marine and Aquatic Sciences, 2023)
Coastline changes are a process that occurs continuously due to movement of sediments, ocean currents, waves, and land use. The impact of this process can be in the form of abrasion and accresion. Due to the huge waves on the south coast, the beaches along the Klungkung Regency are often experience abrasion and accresion. Detection of coastline can use remote sensing methods. This study uses Sentinel-2 satellite images with a spatial resolution of 10 ms to extract the coasline of Klungkung Regency in 2015 and 2020. The coastline extraction method used is the threshold value and band ratio approach. In this study, the digital coastline analysis system (DSAS) toolbox was used for coastline change analysis. The analysis result of coastline change in Klungkung Regency in 2015 and 2020 shows that Gunaksa Village experienced the highest abrasion of 108,6 meters, while Negari Village experienced the highest accrestion of 46,98 meters. The highest rate of coastline change in Klungkung Regency is the abrasion range from 0,058 m/year to 1,846 m/year, while those accretion range from 0,055 m/year to 1,084 m/year.